POTENTIAL ANTICANCER ACTIVITY IN-VITRO FROM EXTRACT OF Turbinaria decurrens Bory - Fitriyanti Jumaetri Sami (Faculty of Pharmacy, Hasanuddin University, 2020)
Cancer is one of the biggest causes of death in the world, not least in Indonesia. Brown algae (T. decurrens Bory) is one of the marine organisms that can be used as a source of natural medicinal ingredients. The purpose of this study was to examine the potential cytotoxicity of extracts of n-hexane, ethyl acetate, and methanol from T. decurrens Bory against MCF-7 human breast cancer cells and H460 lung cancer cells. Samples were extracted using multilevel maceration methods using n-hexane, ethyl acetate, and methanol. Cytotoxicity activity was carried out by the MTT method (3- (4,5-dimethylthiazolyl-2) -2,5-diphenyltetrazolium bromide). The results showed that all extracts of T. decurrens Bory were potential as anticancer. Ethyl acetate extract can inhibit cancer cells at a concentration of 10 µg / mL with more than 50% cytotoxicity compared to other extracts, both against MCF-7 and H460 cells.